2020
DOI: 10.1108/medar-12-2019-0640
|View full text |Cite
|
Sign up to set email alerts
|

Integrated thinking: measuring the unobservable

Abstract: Purpose The purpose of this paper is to add to the growing literature on integrated thinking and reporting by exploring the challenges of measuring integrated thinking in academic research. It provides a review of previous studies, presents a proxy measure to quantify the level of integrated thinking and investigates companies’ approach towards integrated thinking in practice. Design/methodology/approach Firstly, this study proposes a measure to quantify the level of integrating thinking. Secondly, this stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
45
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(45 citation statements)
references
References 61 publications
(122 reference statements)
0
45
0
Order By: Relevance
“…In detail, joint consideration of Figure 4 and Table 4 specifically clarifies how the principle of IT was practically applied and subsequently represented during the case study, thereby making the unobservable visible, as suggested by previous literature (e.g., Malafronte & Pereira, 2021). From a technical point of view, the stock and flow diagram and the discussion among the owners that stemmed from its development and analysis allowed not only describing the complexity embedded in this domain (through the concepts of stocks and flows, causal connections, and polarities of causal linkages) but also identifying where trade-offs among capitals, processes, and units are active across the whole company (see Figure 5 for an example of a feedback loop used to address the concept of trade-off).…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…In detail, joint consideration of Figure 4 and Table 4 specifically clarifies how the principle of IT was practically applied and subsequently represented during the case study, thereby making the unobservable visible, as suggested by previous literature (e.g., Malafronte & Pereira, 2021). From a technical point of view, the stock and flow diagram and the discussion among the owners that stemmed from its development and analysis allowed not only describing the complexity embedded in this domain (through the concepts of stocks and flows, causal connections, and polarities of causal linkages) but also identifying where trade-offs among capitals, processes, and units are active across the whole company (see Figure 5 for an example of a feedback loop used to address the concept of trade-off).…”
Section: Discussionmentioning
confidence: 79%
“…To reach the aims aforementioned, however, IT cannot remain a “nice” theoretical principle; rather it has to be interiorized and become part of the internal culture of an organization (Dumay & Dai, 2017; Feng et al, 2017) and of its way of thinking, making decisions, and acting (La Torre et al, 2019). In this way, IT would help organizations to conceptualize not only the complex pattern of relationships within the organization's business domain but even the unobservable (Malafronte et al, 2020; Malafronte & Pereira, 2021). In the end, as argued by IIRC (IIRC, 2021, p. 3) “the more that integrated thinking is embedded into an organization's activities, the more naturally will the connectivity of information flow into management reporting, analysis and decision‐making.”…”
Section: Integrated Reporting and The Principle Of Integrating Thinkingmentioning
confidence: 99%
“…While Serafeim (2015) adopted the corporate governance score (CGVS) data item from the Asset4 database as a proxy for integrated reporting, De Villiers et al (2017) analyzed the CGVS Asset4 components and observe that “all four drivers and two of the eight outcomes refer to integration” and the remaining six refer to the “reporting outcomes” (p. 948). Therefore, De Villiers et al (2017) conclude that CGVS components measure integrated thinking in a firm (performance) rather than the quality of integrated reports (disclosure) (Venter et al , 2016; Maniora, 2017).…”
Section: The Emerging Literature On Integrated Thinkingmentioning
confidence: 99%
“…The 2018 top 100 market capitalisation of Malaysian public listed organisations (PLCs) is benchmarked as a sample for this study of listed companies from 2014 to 2018. IT is measured in the form of values or percentage, which is aggregated from the developed IT index score intended by the IIRC (Malafronte and Pereira, 2020; Guthrie et al , 2017; Venter et al , 2016; De Villiers et al , 2016). The IT index score is proxied by 12 data items that are relevant to analyse IT under the cluster of Corporate Governance Vision and Strategies (CGVS) (Serafeim, 2015; Venter et al , 2016; Busco et al , 2019).…”
Section: Methodsmentioning
confidence: 99%